A comparison of the effects of maternal anxiety and depression on child development. (13th November 2019) - Gete, S; Calderon-Margalit, R; Grotto, I; Ornoy, A
Abstract: Background: Most studies on the association between the mental health of mothers and the development of their offspring have focused on maternal depression, but only a few have investigated the association between maternal anxiety and child development. We aimed to compare the associations between maternal depression and anxiety symptoms 6-8 weeks postpartum and infant development at 1 year. Methods: We conducted a longitudinal study of 396 mother-child dyads. The mothers were recruited after birth in 3 different hospitals in Israel in 2017 and were followed for one year. Mothers were assessed by completing the General Anxiety Disorder-7 (GAD-7) questionnaire and the Edinburgh Postnatal Depression Scale (EPDS) 6-8 weeks postpartum. Child development was assessed by the Ages & Stages Questionnaires (ASQ-3) at 12 months. Multivariate linear regressions were used to explore the relationship between the EPDS and GAD-7 scores and child development, all as continuous variables, adjusting for maternal education, parity, and gender. Results: Depressive symptoms postpartum were only associated with poor personal-social skills (β=-0.5, 95% CI: -0.91, -0.08). Increasing maternal anxiety was associated with poorer development in communication skills (β =-0.48, 95% CI: -0.93, -0.04), personal-social skills (β =-1.02, 95% CI: -1.58, -0.46), solving problems skills (β =-0.7, 95% CI: -1.27, -0.14) and fine motor skills (β =-0.46, 95% CI: -0.9, -0.02). Neither anxiety nor depressive symptoms were associated with gross motor skills. Controlling for quality of attachment, the associations of depression and anxiety with development were no longer significant, suggesting mediation. Conclusions: Postpartum anxiety was a stronger predictor of low developmental scores than depression, and associations were probably mediated by impaired attachment. Identifying and supporting mothers experiencing anxiety after birth may mitigate the risk of developmental delays in children. Key messages: Maternal anxiety was found to be a significant risk factor for developmental delay at 1 year of age. The association between maternal anxiety and child development was probably mediated by attachment.